Phlebotominae Sand Flies in Paraguay. Abundance Distribution in the Southeastern Region - Salomón, Oscar Daniel (2003)
From September 1993 to August 2001, 7,190 phlebotomine were collected with CDC light trap in an endemic area for human leishmaniasis, in the departments of Misiones and Itapúa, Paraguay. Eleven species were identified: Lutzomyia neivai (93.7%), L. whitmani (4.1%), and L. fischeri, L. shannoni, L. migonei, L. misionensis, L. cortelezzii, L. pessoai, L. alphabetica, Brumptomyia avellari and B. guimaraesi (less than 1%). The last three species are new records for the country. The biodiversity and phlebotomine abundance were associated with the proximity to primary forest or gallery forest, but L. neivai was also found in peridomestic periurban environment. L. neivai was found throughout the year, and showed a period of higher activity from September to April (spring to fall) with a unimodal or bimodal pattern in relation to the annual rainy peaks during the summer. Background literature about phlebotomine from Paraguay has been reviewed.